Nano-reinforcement in sustainable polymer composites - Muhammad Khusairy, Bakri; Md. Rezaur, Rahman; Siti Noor Linda, Taib; Law, Perry Nyuk Khui; Akshay, Kakar; Elammaran, Jayamani (Elsevier Ltd, 2021)
In this chapter, nano-reinforcement in sustainable composites is highlighted by understanding the different types of nonrenewable and renewable nano-reinforcements and its applications in polymer composites. Most of the known nano-reinforcement for nonrenewable are unbiodegradable, expensive, and unsustainable, while the alternative nano-reinforcement for renewable are biodegradable, cheap, and sustainable. Determining the relationship and characteristic of nonrenewable nano-reinforcement may help improve distinctive properties of the materials, in terms of mechanical, morphological, thermal, etc. Therefore understanding the basic properties of the nano-reinforcement helps determining the area of suitable applications.